An investigation of the potato eIF4E isoforms as targets for non-transgenic CRISPR/Cas9 genome editing for viral resistance - Hurst, Rebecca (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScAgric)--Stellenbosch University, 2022.